MSC-ACE2 Ameliorates Streptococcus uberis-Induced Inflammatory Injury in Mammary Epithelial Cells by Upregulating the IL-10/STAT3/SOCS3 Pathway - Yan, Shuping; Zhang, Chonghao; Ji, Xiaoxia; Wu, Gang; Huang, Xinhe; Zhang, Yafeng; Zhang, Yuanshu (Frontiers in Immunology, 2022)
In the dairy industry, Streptococcus uberis (S. uberis) is one of the most important pathogenic bacteria associated with mastitis in milk-producing cows, causing vast economic loss. As of now, the only real effective method of treating and preventing streptococcal mastitis is antimicrobial therapy. In many inflammatory diseases, mesenchymal stem cells (MSC) and angiotensin-converting enzyme 2 (ACE2) play an anti-inflammatory and anti-injurious role. Accordingly, we hypothesized that MSCs overexpressing ACE2 (MSC-ACE2) would ameliorate the inflammatory injury caused by S. uberis in mammary epithelial cells than MSC alone. By activating the IL-10/STAT3/SOCS3 signaling pathway, MSC-ACE2 inhibited the NF-κB, MAPKs, apoptosis, and pyroptosis passways. Moreover, MSC-ACE2 overturned the downregulation of Occludin, ZO-1, and Claudin-3 expression levels caused by S. uberis, suggesting that MSC-ACE2 promotes the repair of the blood-milk barrier. MSC-ACE2 demonstrated greater effectiveness than MSC alone, as expected. Based on these results, MSC-ACE2 effectively inhibits EpH4-Ev cells inflammatory responses induced by S. uberis, and would be an effective therapeutic tool for treating streptococcal mastitis.